Moderate and high intensity exercise improves glycaemia, blood pressure and body composition in menopausal women with type 2 diabetes (Research, Society and Development, 2021)
Post-menopausal women are at high risk of developing type 2 diabetes mellitus (T2DM) and cardiovascular diseases. Regular physical activity is recommended for treatment of chronic diseases. However, there is still no consensus about the intensity and type of exercise. This study aimed to evaluate the effects of combined functional training intensity on the cardiometabolic parameters of post-menopausal women with T2DM. Ninety-eight post-menopausal women with T2DM enrolled in the public health service of a Brazilian municipality were invited to participate in this study. Sixteen volunteers were divided into the moderate (MI) and high intensity (HI) groups. Functional training was performed 3 times a week. Anthropometric data, blood pressure, heart rate (HR), plasma glucose, glycated haemoglobin, total cholesterol, HDL-C, LDL-C and triacylglyceride (TG) levels were measured. Functional training reduced glycated haemoglobin and blood pressure levels and improved body composition in both groups. HI training improved HDL-C and TG levels, although a reduction in LDL-C was observed only in the MI group. Physical training did not modify the other evaluated parameters. The data showed that 8 weeks of functional training, regardless of intensity, is an effective strategy to improve glucose control and promote health benefits in post-menopausal women with T2DM.